Akibat Hukum Majelis Pengawas Daerah Notaris tidak Menyampaikan Hasil Pemeriksaan terhadap Laporan Masyarakat (Studi Putusan No 161/Pdt/2018/PT.Mdn) - suprayitno; Tommy Sambahar Matondang; Rosnidar Sembiring (CV Rewang Rencang, 2025)
Articles 70 and 71 of the Notary Law regulate the authority and obligations of the Regional Supervisory Board (MPD) as the supervisory body for Notaries in Regencies/Cities. This descriptive analytical research using a normative legal approach examines the reporter's rights regarding MPD examination results, legal consequences of non-disclosure of examination results, and legal considerations in Decision No 161/PDT/2018/PT.Mdn. Reporters have the right to know the progress and final results of their report examination. The MPD's failure to communicate examination results constitutes maladministration that violates legal obligations and results in reporters losing their rights. In this decision, the Panel of Judges determined that the report did not meet administrative requirements, thus the MPD had the right not to proceed with material examination.